Synthesis of Ru(III) and Al(III) Complexes Containing Anthraquinone Moiety and Interactions of the UV Radiations - YILDIZ, EMEL; BOZKURT, GOKHAN (Asian Journal of Chemistry, 2010)
The purpose of this study is to synthesize Ru(III) and Al(III) complex compounds of alizarin moiety as UV-absorber and investigated their UV interactions. Ru(III) and Al(III) complexes of alizarin and alizarin sulfonic acid sodium salt were synthesized in basic medium. Their structures were determined by 1H NMR, FT-IR and magnetic susceptibility methods. The synthesized complex compounds and chosen compounds which are anthraquinone, alizarin, alizarin sulfonic acid sodium salt, 1,2,5,8-tetrahydroxyantraquinone were investigated whether they have photochromic properties or not. To determine these properties, all the compounds were exposed UV radiation during various irradiation times such as 0, 2, 4, 6 min at 365 nm. It was observed that the solutions of the anthraquinone derivatives are sensitive to UV irradiation in ethyl acetate. It is suggested that the synthesized complexes are able to absorb UV light more than their ligands within 2 min and any significant change could not record about photochromism.